The Impact of Absence and the Ineffable Quality of Protocol. (October 2014) - Oates, Steff
The author considers a relatively unexplored aspect of loss, death, and dying: absence. She describes work with a range of clients in which an alternative or addition to the author's repertoire of script and game analysis or deconfusion of the Child ego state was needed. This approach, which requires more of a wondering receptivity and an accompaniment without expectation, is particularly appropriate with clients who need to find meaning of their own around considerable gaps in their upbringing. The article challenges the assumption that personality is formed though injunctions, counterinjunctions, and drivers in response to significant others. Readers are invited to consider how much of who we are is formed beyond what is spoken or modeled by others. Consideration is given to Berne's (1963/1975) theory of protocol as forming the essence or atmosphere that is absorbed into our very being.